Allergenomics and analysis of causes of unintentional incorpo‑ ration of substances capable of causing IgE‑mediated food allergy into meat products - E. V. Kryuchenko; Yu. A. Kuzlyakina; V. S. Zamula; I. M. Chernukha (Теория и практика переработки мяса)
The article discusses the definition and mechanism of IgE‑mediated food allergy, provides an overview of the legal regulation of the production and labeling of allergen-containing food products. In order to prevent the inadvertent appearance of allergens in products during their production, an allergenomics procedure is required — a comprehensive assessment of the allergic potential of a food product: allergenicity of product ingredients, risk analysis, and the procedure for managing allergens in the production.